Selbstbild und erektile Dysfunktion 45-jähriger Männer = Self-concept and erectile dysfunction in 45-year-old men - Koegel, A.M.; Hadaschik, Boris; Hohenfellner, Markus (Der Urologe, 2016)
BackgroundSelf-concept consists of self-perceptions and is influenced by the life course of the person.ObjectivesThis study investigated associations between self-concept and erectile dysfunction (ED) in 45-year-old German men.Materials and methodsForty-five-year-old, heterosexual men who had participated in the PROBASE-study were included. Erectile Function was evaluated using the International Index of Erectile Function (IIEF-6). The presence of ED was defined by IIEF-6 score ≤ 25. Self-concept was assessed using the facets “body image” (three items from the Dresden Body Image Inventory, DKB-35), “perception of masculinity” (three items from the Male Role Norms Scale, MRNS), “perceived social pressure with regard to sexual performance” (four newly constructed items), and “sexual self-esteem” (three newly constructed items). Scores for these facets of self-concept can range from 1 to 5. Higher scores indicate a more positive body image, higher sexual self-esteem, a more modern understanding of masculinity, and greater perceived social pressure. Differences in self-concept between men with ED and without ED were analyzed using the Mann-Whitney-U-test. Furthermore, Cohen’s d effect sizes (ES d) were calculated.ResultsThe responses of 3143 men were analyzed. Men with ED (16.2 %) have significantly lower scores regarding body image (mean 3.6 ± 0.6 vs 3.8 ± 0.5; p < 0.001; ES d = −0.5), perception of masculinity (mean 3.4 ± 0.7 vs 3.7 ± 0.6; p < 0.001; ES d = −0.4), and sexual self-esteem (mean 3.6 ± 0.6 vs 3.9 ± 0.5; p < 0.001, ES d = −0.4) than men without ED. Furthermore, they had significantly higher scores for perceived social pressure (mean 2.1 ± 0.7 vs 1.5 ± 0.5; p < 0.001; ES d = 1.2).ConclusionsSelf-concept and ED are associated in 45-year-old men. Men with ED have a more negative body image, a more traditional understanding of masculinity, more negative sexual self-esteem, and greater perceived social pressure with regard to sexual performance than men without ED.
Gesehen am 29.11.2017